Analisis Usaha Keripik Singkong Merk Pedas Gila Pada Kecamatan Tenggarong Kabupaten Kutai Kartanegara - Damayanti, Arista Damayanti (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2016)
Analysis of Income in the Business Cassava Chips Brand Pedas Gila in Distric Tenggarong, Kutai Kartanegara.The purpose of this research was to know income and feasibility from household industry Cassava Chips Brand Pedas Gila in Distric Tenggarong, Kutai Kartanegara,The result of this research showed the receipts from household industry Cassava Chips Brand Pedas Gila is Rp. 20.000.000,-, income is Rp. 8.367.332,-, in 20 time processes during one month with overall cost is Rp. 11.632.668,-. R/C ratio was 1,72>1 this mean that the effort was feasible.Key word : Cassava chip, income, feasibility.